Assessment of nutritional status and body somatotypes in relation to weight changes among overweight and obese office workers in Kota Bharu, Kelantan - Hapizudin, Nurul Asyifa Ezrin Ahmad (Universiti Sains Malaysia, 2016)
The objective of this study was to assess the relationship between body somatotypes with weight changes in overweight and obese office workers in Kota Bharu. A total of 97 overweight and obese office employees from nine government agencies in Kota Bharu, Kelantan were recruited. Anthropometric measurements such as body weight, stature, skinfolds (triceps, subscapular, supraspinale and medial calf), bone breadth and limb girth were taken to determine their body mass index (BM1) and body somatotypes. Short Form - International Physical Activity Questionnaire (IPAQ) was used to determine respondents’ physical activity level. Food Frequency Questionnaire (FFQ) was also used to determine the dietary pattern of respondents. The respondents were assigned to two different groups (intervention and control). Respondents in intervention group were provided with portion plate with guideline to use it and were advised to apply it to control their meal portion and food intake. Among respondents, 35.1% are male and 64.9% are female, with 27.8% were classified as overweight and 72.2% were obese according to World Health Organization (WHO). Body somatotype results showed that respondents were mainly endomorph and mesomorph and no ectomorph. The findings were 64.8% and 35.2% who were endomorph and mesomorph, respectively. In terms of physical activity, 17.8% has low physical activity level, and 58.9% and 23.3% has moderate and high physical activity level, respectively. There is no significant different observed on weight changes between endomorph and mesomorph, as well as between overweight and obese respondents. Weight and BM1 were significantly reduced in intervention group (-2.3 ± 2.2, p<0.001 and -0.9 ± 0.8, p<0.00l) but no significant changes observed in control group.